Studi Hubungan Internasional di Indonesia - Agus Subagyo (Universitas Jenderal Ahmad Yani, 2016)
This paper would like to analyze the development of study of International Relations in Indonesia which has progressed very rapidly. The science of lucrative International Relations since April 1919 in Britain and into Indonesian territory since the 1945’s, has been in great demand by the public, gaining a place in the hearts of the social scientific community, and contributing a lot to the foreign decision-making played by the government. Therefore, it is important to look at opportunities, challenges, and prospects for the development of International Relations studies in Indonesia to date.